A Study on Evaluation of Drug-Drug Interactions in Cardiovascular Disease Patients in a Tertiary Care Hospital - Shaik, Saddam Hussain; A, Ankaiah; M, Rahul; V, Sumanth; M, Siva; G, Lakshmaiah (Learnovate-International, 2025)
Cardiovascular disease remains a major cause of premature mortality and rising health care costs. Cardio metabolic, behavioral, environmental, and social risk factors are major drivers of cardiovascular disease. The present study aimed to assess drug-drug interactions in cardiovascular disease patients in a tertiary care hospital. 36-46 years age patients were more 59 (34.70%) as compared to 47-56 years age patients were 44 (25.88%), 57-67 years age patients were 42 (24.70%). Moderate drug-drug interaction patients were more 81 (47.64%) as compared to other drug interactions. Aspirin + Clopidogrel drugs drug interactions were more 74 (43.52%) as compared to other drug interactions. The study found that incidence of drug interactions was associated with old age, polypharmacy and increased lengths of hospital stay. The development of such data base in hospitals may help for the surveillance of drug interactions in hospitalized cardiac patients. Patients with cardiovascular disorders are subjected to high risk of potential drug-drug interactions and the number of drugs prescribed and educational level of the prescribers has a high significantly associated with the occurrence of potential drug-drug interactions.